The prognostic value of anterior commissure involvement in T1 glottic cancer: A systematic review and meta‐analysis. (13th November 2019) - Tulli, Michele; Re, Massimo; Bondi, Stefano; Ferrante, Luigi; Dajko, Marianxhela; Giordano, Leone; Gioacchini, Federico M.; Galli, Andrea; Bussi, Mario
Abstract : Objective: The anterior commissure is considered a laryngeal subsite, but it is not taken into account in the current T‐staging system. The impact of anterior commissure involvement (ACI) on the oncologic outcomes of T1 glottic tumors has not been well defined and remains controversial. The aim of this study was to assess the influence of ACI in the prognosis of T1 glottic tumors. Methods: A systematic review and meta‐analysis of observational studies was performed by including studies published up to July 2019. Studies were selected if they had investigated the local control rate (LCR) at 5 years of clinical stage I (T1 and N0) glottic squamous cell carcinoma with and without ACI. The difference in LCR at 5 years between T1 glottic tumors without and with ACI was evaluated. Results: The meta‐analysis showed that the difference in LCR at 5 years between T1 glottic tumors without and with ACI is 12% (95% confidence interval: 8%‐16%, p < 0, 0001, I 2 = 34.81%). Conclusions: Our study pointed out that the anterior commissure involvement is a negative prognostic factor in LCR at 5 years for T1 glottic tumors. Our results suggest the need to consider ACI in the T staging of glottic tumors. Laryngoscope, 130:1932–1940, 2020